E-Commerce and Development Report 2001 / Prepared by the UNCTAD Secretariat - United Nations (2001)
Foreword, Abbreviations, Facts and Figures about Electronic Commerce, Measuring Electronic Commerce, Electronic Commerce and Developing Countries: A Computable General Equilibrium Analysis, Impact of Electronic Commerce on Selected Sectors, Electronic Commerce and Tourism for Developing Countries, Business-to-Business Electronic Marketplaces: Their Nature and Impact and Prospects in Developing Countries, Towards Digital Government, Electronic Commerce Environment and Practices, Overview of Selected Legal and Regulatory Developments in Electronic Commerce, Managing Payment and Credit Risks Online: New Challenges for Financial Service Providers, E-Logistics: Delivering the Goods in E-Commerce, Experiences and Opportunities, E-Commerce in the least Developed Countries, China's ICT Strategy and E-Commerce, Conclusion, Notes, References.